Silicon nitride material, preparation method thereof and structural member

By developing silicon nitride materials with an average short-axis grain size of less than or equal to 3.5 μm, the problem that existing ceramic materials cannot have both high hardness and high thermal conductivity is solved, and the development of high-performance ceramic materials has been achieved.

CN119775023APending Publication Date: 2025-04-08BYD CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411846433.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing alumina and aluminum nitride materials have their own advantages and disadvantages, and cannot have both high hardness and high thermal conductivity, making it difficult to meet the demand for ceramic materials in the high-tech field.

Method used

A silicon nitride material is developed, which includes silicon nitride crystals whose average short-axis grain size is less than or equal to 3.5 μm. By controlling the grain size and the composition of the grain boundary phase, the high hardness and high thermal conductivity of the material are achieved.

Benefits of technology

It realizes the high hardness and high thermal conductivity of silicon nitride materials, and is suitable for structural parts such as electrostatic suction cups in high temperature environments, improving the overall performance and application range of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775023A_ABST
    Figure CN119775023A_ABST
Patent Text Reader

Abstract

The invention provides a silicon nitride material and a preparation method thereof, and a structural member, the silicon nitride material comprises a silicon nitride crystal, and the average minor axis grain size of the silicon nitride crystal is less than or equal to 3.5 [mu] m. The silicon nitride material provided by the invention comprises the silicon nitride crystal, the average short-axis grain size of the silicon nitride crystal is smaller than or equal to 3.5 microns, and the grain size is small, so that concentrated stress can be effectively reduced, dislocation slippage can be retarded, defects and discontinuity at a grain boundary can be reduced, a phonon transmission path is optimized, and the service life of the material is prolonged. Therefore, the silicon nitride material has the characteristics of high hardness and high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic materials, and in particular relates to a silicon nitride material and a preparation method and a structural part thereof. Background Art

[0002] With the development of modern high-tech, ceramic materials have gradually become key materials for the development of many high-tech fields, and are widely used in various fields of the national economy such as national defense, chemical industry, metallurgy, electronics, machinery, aviation, aerospace, biomedicine, etc.

[0003] However, the commonly used aluminum oxide and aluminum nitride materials have their own advantages and disadvantages: aluminum oxide has high hardness and stability, but low thermal conductivity; aluminum nitride has excellent thermal conductivity, but insufficient hardness. Therefore, it is urgent to develop a ceramic material with both high hardness and high thermal conductivity. Summary of the invention

[0004] The main purpose of the present invention is to provide a silicon nitride material having both high hardness and high thermal conductivity.

[0005] The present invention also provides a method for preparing the silicon nitride material, which can prepare the above silicon nitride material with simple process and low cost.

[0006] The present invention also provides a structural component, comprising the above silicon nitride material. Therefore, the performance of the silicon nitride material related to the structural component is relatively excellent.

[0007] In a first aspect, the present invention provides a silicon nitride material, wherein the silicon nitride material comprises silicon nitride crystals, wherein the average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm.

[0008] The silicon nitride material as described above, wherein the average long-axis grain size of the silicon nitride crystals is less than or equal to 8.5 μm;

[0009] and / or, the difference between the maximum short-axis grain size and the minimum short-axis grain size of the silicon nitride crystal is less than or equal to 8.5 μm;

[0010] And / or, the difference between the maximum long-axis grain size and the minimum long-axis grain size of the silicon nitride crystal is less than or equal to 10 μm.

[0011] The silicon nitride material as described above, wherein the thermal conductivity of the silicon nitride material is greater than or equal to 90 W / m·K;

[0012] And / or, the Vickers hardness HV10 of the silicon nitride material is greater than or equal to 1600;

[0013] And / or, the density of the silicon nitride material is greater than or equal to 3.21 g / cm 3 ;

[0014] And / or, the flexural strength of the silicon nitride material is greater than or equal to 900 MPa.

[0015] The silicon nitride material as described above, wherein the β-Si 3 N 4 The mass percentage is greater than or equal to 95%.

[0016] As described above, the silicon nitride material has a grain boundary phase between the silicon nitride crystals, the grain boundary phase includes a glass phase, and the glass phase includes at least one of Mg, Ca, Zr, La, Ce, Y, Yb, Eu, Dy, Lu, B, and Ti.

[0017] In a second aspect, the present invention provides a method for preparing the silicon nitride material as described above, comprising the following steps:

[0018] 1) contacting a raw material including silicon powder with a nitrogen source to perform a nitridation reaction to obtain a precursor containing silicon nitride; the precursor containing silicon nitride includes β-Si 3 N 4 and α-Si 3 N 4 , the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 0.57-0.86;

[0019] 2) Sintering the precursor containing silicon nitride to obtain the silicon nitride material.

[0020] In the preparation method as described above, the raw material including silicon powder also includes at least one of a reinforcing phase, a sintering aid, a dispersant, a binder, a plasticizer, and a defoaming agent;

[0021] The reinforcement phase includes TiC and / or TiN.

[0022] The preparation method as described above, before the nitridation reaction, also includes: sequentially performing a casting process and a debinding process on the raw material including silicon powder to obtain a debinding product; and contacting the debinding product with a nitrogen source to perform a nitridation reaction to obtain the precursor containing silicon nitride.

[0023] According to the preparation method described above, the D50 of the silicon powder is 0.9 μm-15 μm, preferably 2.0 μm-6.5 μm;

[0024] And / or, the sintering temperature is 1700°C-1900°C.

[0025] In the preparation method as described above, the nitridation reaction process comprises:

[0026] 1) contacting the raw material including silicon powder with a nitrogen source, and performing a first reaction at 1200° C.-1250° C. to obtain a first reaction product; wherein the first reaction product contains β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 0.04-0.54;

[0027] 2) subjecting the first reaction product to a second reaction at 1300°C-1350°C to obtain a second reaction product; wherein the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 0.33-0.82;

[0028] 3) subjecting the second reaction product to a third reaction at 1400° C.-1500° C. to obtain the precursor containing silicon nitride.

[0029] In a third aspect, the present invention provides a structural component, comprising the silicon nitride material as described above or the silicon nitride material prepared by the preparation method as described above.

[0030] The structural component as described above is at least one of an electrostatic chuck, a ceramic substrate, a ceramic bearing ball, a ceramic bearing sleeve, and a protective tube.

[0031] The silicon nitride material provided by the present invention includes silicon nitride crystals. The average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm. The small grain size can not only effectively reduce concentrated stress and block dislocation slip, but also reduce defects and discontinuities at grain boundaries and optimize phonon transmission paths, so that the silicon nitride material can have the characteristics of high hardness and high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 A schematic diagram of an electrostatic chuck provided by the present invention;

[0034] Figure 2 A schematic diagram of the main structure of an electrostatic chuck provided by the present invention;

[0035] Figure 3 This is a scanning electron microscope image of the silicon nitride material of Example 1 of the present invention;

[0036] Figure 4 This is a scanning electron microscope image of the silicon nitride material of Example 2 of the present invention;

[0037] Figure 5 This is a scanning electron microscope image of the silicon nitride material of Example 3 of the present invention;

[0038] Figure 6 This is a scanning electron microscope image of the silicon nitride material of Comparative Example 3 of the present invention;

[0039] Figure 7 This is a scanning electron microscope image of the aluminum oxide material of Comparative Example 5 of the present invention;

[0040] Figure 8 This is a grain size distribution diagram of the silicon nitride material of Example 1 of the present invention;

[0041] Fig. 9 is a grain size distribution diagram of the silicon nitride material of Example 2 of the present invention;

[0042] Fig.10 This is a grain size distribution diagram of the silicon nitride material of Example 3 of the present invention;

[0043] Fig.11 This is a grain size distribution diagram of the silicon nitride material of Comparative Example 3 of the present invention;

[0044] Fig.12 This is a physical picture of the silicon nitride ceramic green sheet of Comparative Example 2 of the present invention;

[0045] Fig.13 This is a physical picture of the silicon nitride material of comparative example 4 of the present invention. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Ceramic materials are widely used in various fields of the national economy due to their advantages such as high melting point, high hardness, high wear resistance and oxidation resistance. Currently, the commonly used alumina material has high hardness and stability, but low thermal conductivity; aluminum nitride material has excellent thermal conductivity, but insufficient hardness.

[0048] Specifically, the manufacturing process of semiconductor products is complex, and the wafers need to be moved, processed, and tested between multiple process equipment. During this process, the wafers need to be stably fixed. The electrostatic chuck is a process element used to clamp the wafer in integrated circuit (IC) manufacturing processes such as etching, physical vapor deposition (PVD), and chemical vapor deposition (CVD). It is one of the most core components in the semiconductor manufacturing process. Compared with traditional mechanical chucks or vacuum chucks, Figure 1 The electrostatic chuck shown can effectively clamp the wafer, making the force distribution more even, avoiding damage to the wafer caused by pressure, collision and other reasons during the use of the traditional mechanical chuck. It can also effectively avoid wafer warping due to contact stress, reduce particle contamination, and increase the processing area of ​​the wafer. At the same time, it overcomes the defects of vacuum chucks such as not being able to be used in low-pressure environments and not being able to effectively control the wafer temperature through back-blowing gas. Therefore, electrostatic chucks are replacing traditional mechanical chucks and vacuum chucks and becoming the first choice in semiconductor manufacturing processes. Figure 2 As shown in the figure, the clamping system of the electrostatic chuck is similar to a sandwich structure, which consists of an electrolyte adsorption layer, an electrode layer, and a base layer from top to bottom. The three parts are stacked together in a layered structure. Among them, the electrolyte adsorption layer is the core of the electrostatic chuck, usually made of ceramic materials such as aluminum oxide or aluminum nitride, and plays the role of electrostatic induction, support, and heat conduction, which directly determines the performance of the electrostatic chuck.

[0049] Specifically, Al 2 O 3 The suction cup has high hardness and good stability, but poor thermal conductivity, only 20W / m·K~30W / m·K, which makes it difficult to ensure temperature uniformity on the wafer surface, and has an adverse effect on the processing stability and accuracy of the wafer. Although the AlN suction cup has good thermal conductivity, up to 170W / m·K~200W / m·K, its narrow bandgap causes its resistivity to drop sharply above 400°C, and it cannot work effectively at high temperatures. In addition, its hardness is low and its stability is poor, making it difficult to meet the needs of the development of advanced semiconductor process technology.

[0050] Based on this, in the first aspect, the present invention provides a silicon nitride material, the silicon nitride material includes silicon nitride crystals, and the average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5μm, for example, it can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm or a range consisting of any two of them.

[0051] The silicon nitride material of the present invention includes silicon nitride crystals, and the average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm, so that the silicon nitride material has the characteristics of high hardness and high thermal conductivity. The reason is that: a smaller grain size means more grain boundaries, which can hinder dislocation movement. At the same time, smaller grains can increase the number of grains per unit volume, make the force more dispersed, and effectively reduce the risk of stress concentration, thereby improving the toughness and hardness of the silicon nitride material and improving the density of the silicon nitride material. In addition, a smaller grain size can reduce defects and discontinuities at the grain boundaries, optimize the phonon transmission path, and thus improve the thermal conductivity of the silicon nitride material. In addition, the refined grain size helps to improve the uniformity and stability of the material, prevent local uneven thermal expansion, thereby improving the thermal stability of the material, reducing the tendency of the material to grow grains at high temperatures, and maintaining the stability of its mechanical and thermal properties.

[0052] The silicon nitride material provided by the present invention includes silicon nitride crystals, and the average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm. The small grain size can not only effectively reduce concentrated stress and block dislocation slip, but also reduce defects and discontinuities at grain boundaries and optimize phonon transmission paths, so that the silicon nitride material can have the characteristics of high hardness and high thermal conductivity. The silicon nitride material is used for structural parts, such as electrostatic chucks, which can make the electrostatic chucks work stably in the range of 300°C-600°C, with better positioning accuracy and no obvious attenuation of resistivity at high temperatures. In the process of high-temperature ion implantation, the positioning accuracy and temperature uniformity of the wafer can be significantly improved, and the processing accuracy and yield can be improved.

[0053] In some embodiments of the present invention, the average long axis grain size of the silicon nitride crystal is less than or equal to 8.5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 8.5 μm or a range consisting of any two thereof.

[0054] In some embodiments, the difference between the maximum short-axis grain size and the minimum short-axis grain size of the silicon nitride crystal is less than or equal to 8.5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 8.5 μm or a range consisting of any two of them.

[0055] In some embodiments, the difference between the maximum long-axis grain size and the minimum long-axis grain size of the silicon nitride crystal is less than or equal to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range consisting of any two of them.

[0056] In the present invention, the average long-axis grain size of the silicon nitride crystal, the difference between the maximum short-axis grain size and the minimum short-axis grain size, and the difference between the maximum long-axis grain size and the minimum long-axis grain size are within the above ranges, which can ensure uniform distribution of stress in the crystal and reduce local stress concentration, thereby improving the overall strength and durability of the material and improving fracture toughness. The smaller grain size difference reduces phonon scattering at the grain boundary, thereby improving the thermal conductivity of the material.

[0057] In some embodiments of the present invention, the thermal conductivity of the silicon nitride material is greater than or equal to 90 W / m·K. For example, it can be 90 W / m·K, 91 W / m·K, 93 W / m·K, 95 W / m·K, 100 W / m·K, 110 W / m·K, 120 W / m·K, 130 W / m·K, 140 W / m·K, 150 W / m·K or a range consisting of any two of them.

[0058] The thermal conductivity of the silicon nitride material in the present invention is within the above range, which means that the material can conduct heat quickly and effectively, helps prevent overheating and heat accumulation, maintains uniform temperature distribution, reduces local overheating, and reduces the risk of material cracking or deformation.

[0059] In some embodiments, the Vickers hardness HV10 of the silicon nitride material is greater than or equal to 1600, for example, may be 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950, 2000 or a range consisting of any two thereof.

[0060] The hardness HV10 of the silicon nitride material in the present invention is within the above range, so that it has excellent wear resistance, the risk of surface damage is significantly reduced, and the material can withstand large mechanical loads without deformation or fracture.

[0061] In some embodiments, the density of the silicon nitride material is greater than or equal to 3.21 g / cm 3 , for example, can be 3.21 g / cm 3 , 3.25g / cm 3 , 3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3 、3.45g / cm 3 , 3.5g / cm 3 Or a range consisting of any two of them.

[0062] The density of the silicon nitride material in the present invention is within the above range, which means that the porosity inside the material is relatively low, which helps to improve the strength and hardness of the material. Fewer pores can reduce stress concentration points, thereby improving the compressive and bending strengths of the material. The material has good thermal stability and can distribute heat more evenly, reducing thermal stress caused by uneven thermal expansion. It also helps to reduce obstacles in the heat conduction path, such as pores, thereby improving the thermal conductivity of the material.

[0063] In some embodiments, the flexural strength of the silicon nitride material is greater than or equal to 900 MPa, for example, 900 MPa, 950 MPa, 1000 MPa, 1050 MPa, 1100 MPa, 1200 MPa, 1300 MPa, 1400 MPa, 1500 MPa or a range consisting of any two thereof.

[0064] The flexural strength of the silicon nitride material in the present invention is within the above range, and can withstand a large load without breaking or deforming, and can improve impact resistance to a certain extent, and can still maintain its strength at high temperatures, reducing the risk of breakage and failure.

[0065] In some embodiments of the present invention, the β-Si 3 N 4 The mass percentage of β-Si is greater than or equal to 95%. 3 N 4 It has very high mechanical strength and toughness, can withstand high stress without breaking, exhibits excellent thermal stability in high temperature environments, can withstand extreme temperatures without significant performance changes, and has high thermal conductivity, which can effectively dissipate heat.

[0066] Among them, the columnar β-Si 3 N 4 The length of the short side is the short axis grain size of the silicon nitride crystal, and the length of the long side is the long axis grain size of the silicon nitride crystal. 3 N 4 The length of the short side is averaged to obtain the average short axis grain size of the silicon nitride crystal; test multiple β-Si 3 N 4 The length of the long side is averaged to obtain the average long axis grain size of silicon nitride crystal. 3 N 4 Among the lengths of the short sides, the largest is the maximum short-axis grain size, and the smallest is the minimum short-axis grain size; multiple β-Si 3 N 4 Among the lengths of the long sides, the largest one is the maximum long-axis grain size, and the smallest one is the minimum long-axis grain size.

[0067] In some embodiments of the present invention, there is a grain boundary phase between silicon nitride crystals, the grain boundary phase includes a glass phase, and the glass phase includes at least one of Mg, Ca, Zr, La, Ce, Y, Yb, Eu, Dy, Lu, B, and Ti.

[0068] Among them, the metal elements in the sintering aid and the metal elements in the reinforcing material and elements such as oxygen and silicon form a glass phase that exists in the grain boundary phase between silicon nitride crystals, which can reduce the sintering temperature of silicon nitride, promote liquid phase sintering, obtain higher density silicon nitride materials, and improve their mechanical strength and toughness.

[0069] The grain size of the silicon nitride material prepared by the present invention is controllable, and the silicon powder can be nitrided in situ, the silicon powder nitridation rate can be controlled, and the silicon powder can be converted into α-Si 3 N 4 、α-Si 3 N 4 Conversion of β-Si 3 N 4 The ratio and β-Si 3 N 4 The nucleation site is regulated to achieve the effect of grain refinement. Compared with Si prepared directly from silicon nitride powder, 3 N 4 The material has an average grain size reduced from 5μm-10μm to below 3.5μm. It uses fine grain strengthening instead of adding aluminum for solid solution strengthening, avoiding the problem of decreased thermal conductivity caused by the introduction of Al in traditional high-hardness silicon nitride ceramics, and achieving both high hardness and high thermal conductivity.

[0070] In a second aspect, the present invention provides a method for preparing the silicon nitride material as described above, comprising the following steps:

[0071] 1) contacting a raw material including silicon powder with a nitrogen source to perform a nitridation reaction to obtain a precursor containing silicon nitride; the precursor containing silicon nitride includes β-Si 3 N 4 and α-Si 3 N 4 , β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 0.57-0.86; for example, it can be 0.57, 0.60, 0.65, 0.70, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86 or a range consisting of any two of them.

[0072] 2) Sintering the precursor containing silicon nitride to obtain silicon nitride material.

[0073] In step 1), the raw materials for preparing silicon nitride materials include silicon powder. Silicon powder is easy to obtain and has a lower oxygen content than silicon nitride powder. With the combined action of sintering aids, it can prevent oxygen atoms from entering the silicon nitride lattice to a certain extent, reduce crystal defects, and facilitate the propagation of heat between grains, thereby obtaining a better thermal conductivity. At the same time, the material with silicon powder as the raw material shrinks less in size during the sintering process. Under the same product size, it is better than that with Si 3 N 4 The yield is higher than that of silicon powder as raw material. Among them, the purity of silicon powder is greater than or equal to 99%, preferably, the purity of silicon powder is greater than or equal to 99.5%; the oxygen content is less than or equal to 2%, preferably, the oxygen content is less than or equal to 1%; the content of other impurities is less than or equal to 1%, preferably, the content of other impurities is less than or equal to 600ppm, to ensure that the surface of the cast sheet does not crack, roughen, etc., and at the same time avoid the performance degradation of the obtained silicon nitride material due to excessive oxygen content and the introduction of impurity elements.

[0074] The raw materials of silicon powder and nitrogen source, such as nitrogen, are contacted for in-situ nitridation, so that silicon powder and nitrogen react to form silicon nitride, thereby obtaining a precursor containing silicon nitride. In the nitridation reaction, nitrogen is charged at 900℃-1200℃, and the pressure is gradually increased with the temperature. During the silicon powder nitridation stage, Si is converted into α-Si 3 N 4 and α-Si 3 N 4 Converted to β-Si 3 N 4 The two processes occur simultaneously, but the conversion of Si to α-Si 3 N 4 Process-based, β-Si 3 N 4 and α-Si 3 N 4 When the mass ratio is less than 1, Si is converted into α-Si 3 N 4 Faster than α-Si 3 N 4 Converted to β-Si 3 N 4 Process. At this stage, the temperature rise ends and all silicon powder is converted into Si 3 N 4 Crystalline phase, partly α-Si 3 N 4 Not yet converted to β-Si 3 N 4 , that is, the β-Si in the obtained precursor containing silicon nitride 3 N 4 and α-Si 3 N4 The mass ratio is 0.75-0.86. Subsequently, as the temperature rises, that is, the sintering treatment, it further transforms and grows in the presence of the liquid phase and eventually becomes dense.

[0075] In step 2), the precursor containing silicon nitride is sintered to make α-Si 3 N 4 Completely converted into β-Si 3 N 4 , and obtain silicon nitride material. Among them, the sintering temperature can ensure that β-Si 3 N 4 The full growth of grains eliminates pores and achieves high densification of silicon nitride materials. This high density helps to improve the mechanical strength and wear resistance of the material, and can effectively control the growth and phase change of grains, reduce defects and pores in the material, and improve the overall quality and performance of the material. The heating rate of the sintering treatment is controlled to be 0.2℃ / min-5℃ / min, and the sintering time is 2h-6h, and then the temperature is lowered. Before 1300℃-1500℃, the temperature is lowered at a certain rate, for example, 1℃ / min-5℃ / min, and then the temperature is lowered to room temperature by natural cooling.

[0076] The method for preparing the silicon nitride material provided by the present invention can prepare the above silicon nitride material, and the silicon nitride material has both high hardness and high thermal conductivity.

[0077] In some embodiments of the present invention, the raw material including silicon powder further includes at least one of a reinforcing phase, a sintering aid, a dispersant, a binder, a plasticizer, and a defoaming agent; and the reinforcing phase includes TiC and / or TiN.

[0078] The raw material including silicon powder of the present invention also includes at least one of a reinforcing phase, a sintering aid, a dispersant, a binder, a plasticizer, and a defoaming agent, wherein the reinforcing phase can significantly improve the mechanical strength and hardness of silicon nitride, making the material wear-resistant. TiC and TiN can hinder the expansion of cracks, thereby improving the fracture toughness of the material, which makes the material less likely to break when subjected to impact and mechanical loads. In addition, TiC and TiN have excellent thermal stability and can maintain their performance in a high temperature environment. This property helps to improve the stability and reliability of silicon nitride ceramics in high temperature applications. At the same time, the reinforcing phase can also improve the thermal conductivity of the material, which is conducive to effective heat dissipation. Si 3 N 4 It is difficult for ceramics to form a dense crystal structure by diffusion during the sintering process, so sintering aids are generally added to form a liquid phase (eutectic molten compound) to provide a medium for rapid material transportation, thereby accelerating the densification process of silicon nitride. Dispersants and binders can improve the uniformity and formability of the material, while plasticizers and defoamers help improve the fluidity of the material and reduce defects.

[0079] The mixed powder of the present invention includes silicon powder, sintering aid and / or reinforcing phase, wherein the mass percentage of silicon powder in the mixed powder is 75%-98%, preferably 86.5%-95%; the mass percentage of sintering aid in the mixed powder is 2%-25%, preferably 5%-11%; the mass percentage of reinforcing phase in the mixed powder is 0.5%-2.5%. The mass percentage of binder in the mixed powder is 12%-40%, preferably 15%-35%; the mass percentage of plasticizer in the mixed powder is 2%-20%, preferably 3%-10%; the mass percentage of dispersant in the mixed powder is 0.5%-5%, preferably 1.5%-3%; the mass percentage of defoamer in the mixed powder is 0.5%-3%, preferably 0.5%-1.5%.

[0080] The sintering aid includes at least one of metal oxides, metal non-oxides, rare earth oxides, and non-metal oxides, wherein the metal oxides include MgO, CaO, ZrO 2 At least one of the metal non-oxides comprises MgSiN 2 , rare earth oxides including La 2 O 3 、Ce 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Eu 2 O 3 、Dy 2 O 3 、Lu 2 O 3 At least one of the non-metallic oxides comprises Si 3 N 4 , B 2 O 3 、SiO 2 Preferably, the sintering aid includes MgO, Y 2 O 3 , Yb 2 O 3 At least one of the above sintering aids can ensure the compactness and performance improvement of the ceramic. Intrinsic high hardness can be achieved without adding Al additives for solid solution strengthening. By optimizing the additives, it is possible to avoid Al solid solution into β-Si 3 N 4 The formation of vacancies and lattice distortion causes a decrease in thermal conductivity, thereby achieving both ultra-high hardness and high thermal conductivity.

[0081] The binder includes at least one of polyvinyl butyral, acrylic resin, and rosin, preferably polyvinyl butyral and / or acrylic resin. The plasticizer includes a primary plasticizer and an auxiliary plasticizer, the primary plasticizer includes at least one of dibutyl phthalate, dioctyl phthalate, diisooctyl phthalate, dimethyl phthalate, diethyl phthalate, dioctyl adipate, triethylene glycol diisooctanoate, and di-n-hexyl adipate, the auxiliary plasticizer includes at least one of epoxidized soybean oil, methyl epoxy, polyethylene glycol, and trioctyl phosphate, preferably, the plasticizer includes at least one of dibutyl phthalate, dioctyl phthalate, triethylene glycol diisooctanoate, and polyethylene glycol. The dispersant includes at least one of castor oil, fatty alcohol polyoxyethylene ether, polyvinyl pyrrolidone, polyether polymer dispersant, and polyester polymer dispersant, preferably at least one of castor oil, polyvinyl pyrrolidone, and polyether polymer dispersant. The defoamer includes at least one of an alkane compound without silicone, an alcohol defoamer, and a phosphate defoamer.

[0082] In some embodiments of the present invention, before the nitridation reaction, the steps further include: sequentially performing a casting process and a debinding process on a raw material including silicon powder to obtain a debinding product; and contacting the debinding product with a nitrogen source to perform a nitridation reaction to obtain a precursor containing silicon nitride.

[0083] Among them, a tape casting machine is used to cast the raw materials including silicon powder, the slurry is lifted by a scraper to control the thickness, and the slurry is dried in a segmented oven with increasing temperature. The belt speed of the tape casting machine is 60mm / min-1000mm / min, and the temperature of the tape casting process is set to increase in the temperature range of 40℃-120℃. The tape casting process can produce thin and uniform silicon nitride materials, ensure the consistency of the thickness and composition of the material, and can accurately control the thickness and shape of the material.

[0084] The temperature of the debinding treatment is 500℃-700℃, and the heating rate is 0.1℃ / min-3℃ / min. The debinding treatment can remove the binder and plasticizer introduced in the production process of silicon nitride materials, ensuring that no harmful gases will be generated or material defects will be caused during the subsequent sintering process, improving the purity of silicon nitride materials, improving their mechanical and thermal properties, and also helping to reduce defects and voids in the molded products, and improving the density and strength of the materials. Among them, the temperature of the debinding treatment is not lower than the decomposition temperature of the binder and plasticizer, and the organic materials such as the binder and plasticizer are decomposed through the debinding treatment.

[0085] In some embodiments of the present invention, the D50 of silicon powder is 0.9 μm-15 μm, for example, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm or any two thereof, preferably 2.0 μm-6.5 μm. This is conducive to the final preparation of silicon nitride material with a small average minor axis grain size, so that the silicon nitride material has both high hardness and high thermal conductivity.

[0086] In some embodiments, the sintering temperature is 1700°C-1900°C, for example, 1700°C, 1710°C, 1730°C, 1750°C, 1800°C, 1850°C, 1900°C or any two thereof. 3 N 4 The full growth of grains eliminates pores and achieves high densification of silicon nitride ceramics. This high density helps to improve the mechanical strength and wear resistance of the material, and can effectively control the growth and phase change of grains, reduce defects and pores in the material, and improve the overall quality and performance of the material.

[0087] In some embodiments of the present invention, the process of the nitridation reaction includes: 1) contacting a raw material including silicon powder with a nitrogen source, and performing a first reaction at 1200°C-1250°C, for example, 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, etc., to obtain a first reaction product; wherein the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of is 0.04-0.54, for example, it can be 0.04, 0.11, 0.20, 0.30, 0.35, 0.39, 0.40, 0.42, 0.45, 0.47, 0.50, 0.52, 0.54, etc.; 2) the first reaction product is subjected to a second reaction at 1300°C-1350°C, for example, it can be 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, etc., to obtain a second reaction product; wherein the β-Si in the second reaction product 3 N 4 and α-Si 3 N 4The mass ratio of is 0.33-0.82, for example, it can be 0.33, 0.35, 0.40, 0.43, 0.50, 0.60, 0.64, 0.66, 0.68, 0.70, 0.72, 0.75, 0.77, 0.80, 0.82, etc.; 3) the second reaction product is subjected to a third reaction at a temperature of 1400°C-1500°C, for example, it can be 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, etc., to obtain a precursor containing silicon nitride.

[0088] The nitridation process of silicon powder occurs at 1200℃-1500℃, with a heating rate of 0.2℃ / min-1℃ / min. In order to control the grain size of the material and avoid abnormal grain growth, stage temperature control is adopted. This process controls the Si and Si 3 N 4 Content and β-Si 3 N 4 and α-Si 3 N 4 The relationship of the mass ratio is shown in the following table:

[0089]

[0090] In order to achieve fine crystallization, the temperature is raised in stages in the nitriding reaction temperature zone of 1200℃-1500℃, with a heating rate of 0.2℃ / min-1℃ / min, and the nitriding rate and degree of silicon powder are controlled so that β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si fluctuates in the range of 0.04-0.86, and the overall 3 N 4 and α-Si 3 N 4 The ratio is less than 1, which ensures that Si→α-Si 3 N 4 The complete transformation of β-Si 3 N 4 This ensures that the in-situ generated silicon nitride has sufficient β-Si 3 N 4 nucleation sites and ensure that β-Si 3 N 4 The growth is suppressed, and finally a fine-grained structure is obtained. The toughness and intrinsic hardness of silicon nitride materials are greatly improved through fine-grain strengthening.

[0091] In the present invention, the above-mentioned programmed temperature rising method is used to carry out the nitridation reaction, which can achieve the β-Si 3 N 4 and α-Si 3 N 4 The mass of fluctuates in the range of 0.04-0.86, ensuring the conversion of Si into α-Si 3 N 4 The complete transformation of β-Si 3 N 4 The gradual generation of the silicon nitride material is conducive to the final preparation of silicon nitride materials with smaller particle sizes. The toughness and intrinsic hardness of silicon nitride materials are greatly improved through fine grain strengthening.

[0092] The specific preparation method of the silicon nitride material of the present invention may include the following steps:

[0093] 1) Add raw materials including silicon powder, sintering aid and / or reinforcing phase into a mixing device for mixing to obtain a mixed powder with a particle size reduced by 10%-20%.

[0094] 2) The first system including the mixed powder, dispersant, part of the solvent and silicon nitride balls is subjected to a first ball milling treatment to obtain a first ball milling slurry; the solid content of the first ball milling slurry is 30%-70%, preferably 37%-50%. The ball-to-material mass ratio of the first ball milling treatment is (1-5):1, the speed of the mixing equipment is 20rpm-100rpm, and the mixing time is 3h-6h.

[0095] 2) The second system including the first ball milling slurry, binder, plasticizer, defoamer and residual solvent is subjected to a second ball milling treatment. After the second ball milling, the slurry is filtered with a filter to obtain a second ball milling slurry; the solid content of the second ball milling slurry is 30%-70%, preferably 37%-50%. The total mass of the solvent accounts for 70%-150% of the mass percentage of the mixed powder, preferably 80%-130%. The solvent includes at least one of ethanol, butanol and ethyl acetate. The mass ratio of part of the solvent to the residual solvent is 9:1-4:6. The single ball milling mixing time is adjusted according to the particle size and solubility of the powder. The single ball milling time does not exceed 48h, the two ball milling times are 24h-96h, and the speed is set to 30rpm-300rpm.

[0096] 3) Degassing the secondary ball-milled slurry under negative pressure and stirring conditions to obtain silicon nitride non-aqueous tape-casting slurry. The pressure of the degassing treatment is less than or equal to -0.1 MPa, the stirring speed of the degassing treatment is 20 rpm-60 rpm, and the degassing treatment time is 1 h-6 h; the dynamic viscosity of the silicon nitride non-aqueous tape-casting slurry at 25°C is 6000 mPa·s-40000 mPa·s, preferably 9000 mPa·s-17000 mPa·s.

[0097] 4) Use a tape casting machine to cast the silicon nitride non-aqueous tape casting slurry. The slurry is lifted by a scraper to control the thickness. It is dried in a segmented oven with increasing temperature to obtain a silicon nitride ceramic green sheet, which is cut according to the required size. The thickness of the silicon nitride ceramic green sheet is 0.2mm-1mm, the accuracy is controlled to 1μm±2%, and the length and width can be cut arbitrarily according to actual needs.

[0098] 5) Silicon nitride ceramic green sheets are isolated and stacked using boron nitride powder and subjected to a debinding treatment in a degreasing furnace to obtain a debinding product.

[0099] 6) The debinding product is subjected to high-pressure nitridation reaction and sintering treatment in sequence to obtain silicon nitride material.

[0100] In a third aspect, the present invention provides a structural component, comprising the silicon nitride material as described above or the silicon nitride material prepared by the preparation method as described above. The structural component has the advantages corresponding to the above silicon nitride material, which will not be described in detail.

[0101] In some embodiments of the present invention, the structural member is at least one of an electrostatic chuck, a ceramic substrate, a ceramic bearing ball, a ceramic bearing sleeve, and a protective tube.

[0102] The specific structural part of the present invention includes the above silicon nitride material, so the silicon nitride material related to the above structural part has excellent performance. For example, the structural part is an electrostatic chuck, that is, the electrolyte adsorption layer of the electrostatic chuck includes silicon nitride material, so the electrostatic chuck has high positioning accuracy and good high temperature stability.

[0103] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0104] Example 1

[0105] The method for preparing the silicon nitride material of this embodiment comprises the following steps:

[0106] 1) The mixed powder includes silicon powder, sintering aid and reinforcing phase. The sintering aid includes Y 2 O 3 、MgO、MgSiN 2 , the reinforcement phase includes TiN. Weigh 447.5g of Si powder (accounting for 89.5% of the mixed powder mass), and the D50 of silicon powder is 2.6μm. 2 O 3 32.5g of powder (accounting for 6.5% of the total weight of the mixed powder), 14.5g of MgO powder (accounting for 2.9% of the weight of the mixed powder), MgSiN 2Powder 3.0g (accounting for 0.6% of the mass of the mixed powder), TiN powder 2.5g (accounting for 0.5% of the mass of the mixed powder), binder polyvinyl butyral 133.5g (accounting for 26.7% of the mass of the mixed powder), plasticizer diisooctyl phthalate 35g (accounting for 7% of the mass of the mixed powder), dispersant polyvinyl pyrrolidone 12.5g (accounting for 2.5% of the mass of the mixed powder), defoaming agent diethyl hexanol 5g (accounting for 1% of the mass of the mixed powder), solvent ethanol 450g (accounting for 90% of the mass of the mixed powder), silicon nitride grinding balls 750g (accounting for 150% of the mass of the mixed powder).

[0107] 2) Add the weighed silicon powder, sintering aid and reinforcing phase into the mixing equipment for mixing, set the speed to 30rpm, mix for 3h, and obtain mixed powder. Then add the mixed powder, silicon nitride grinding balls, dispersant and part of the solvent into the ball mill, and perform a ball milling process at a speed of 60rpm for 36h to obtain a primary ball mill slurry.

[0108] 3) Then, a binder, a plasticizer, a defoaming agent, and the remaining solvent are added to the first ball-milled slurry for a second ball-milling treatment for 36 hours. After the ball-milling is completed, the slurry is filtered to obtain a second ball-milled slurry.

[0109] 4) The secondary ball-milled slurry was degassed for 3 h at a negative pressure of -0.07 MPa and a stirring speed of 30 rpm to obtain a silicon nitride non-aqueous tape-casting slurry having a dynamic viscosity of 11000 mPa·s at 25° C.

[0110] 5) The silicon nitride non-aqueous casting slurry is subjected to a casting process using a casting machine. The belt speed of the casting machine is 300 mm / min. The temperature is set to five temperature zones of 40°C, 50°C, 60°C, 70°C, and 80°C for drying to obtain a silicon nitride ceramic green sheet with a thickness of 0.5 mm.

[0111] 6) Boron nitride powder is used to isolate and stack silicon nitride ceramic green sheets, which are pre-sintered at 550°C in a debinding furnace with a heating rate of 1°C / min to obtain a debinding product.

[0112] 7) The debinding product is nitrided to obtain a precursor containing silicon nitride. The heating rate is 2°C / min, and 1100°C is maintained for 150min, 1200°C is maintained for 120min, 1250°C is maintained for 120min, 1300°C is maintained for 60min, 1350°C is maintained for 300min, 1400°C and 1450°C are maintained for 300min respectively. During the nitriding process, nitrogen is introduced when the temperature rises to 1200°C, and the pressure at 1200°C is controlled to be 0.5MPa, 1250°C is controlled to be 0.5MPa, 1300°C is controlled to be 0.7MPa, 1350°C is controlled to be 0.7MPa, 1400°C is controlled to be 1.0MPa, and 1450°C is controlled to be 1.0MPa. After maintaining 1200°C for 120min, the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.08, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.41, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.43, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.69, and the β-Si was tested after maintaining 1400℃ for 300min. 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.72, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 0.78.

[0113] 8) Sintering the precursor containing silicon nitride to obtain silicon nitride material. The sintering temperature is 1900°C and kept for 3 hours; the temperature is lowered at a rate of 3°C / min to 1400°C; and then the temperature is lowered to room temperature by natural cooling. The silicon nitride material includes silicon nitride crystals, and there are grain boundary phases between the silicon nitride crystals. The grain boundary phases include a glass phase, and the glass phase includes Y, Mg, Si, O, and Ti.

[0114] Example 2

[0115] The preparation method of the silicon nitride material in Example 2 is substantially the same as that in Example 1, except that: in step 1), the sintering aid comprises Y 2 O 3 , MgO, weigh 450g Si powder (accounting for 90% of the mixed powder mass), Y 2 O 3 28.0g of powder (accounting for 5.6% of the mass of the mixed powder), 17.0g of MgO powder (accounting for 3.4% of the mass of the mixed powder), 5.0g of TiN powder (accounting for 1.0% of the mass of the mixed powder), 137.5g of polyvinyl butyral as binder (accounting for 27.5% of the mass of the mixed powder), 27.5g of diisooctyl phthalate as plasticizer (accounting for 5.5% of the mass of the mixed powder), 10.0g of polyvinyl pyrrolidone as dispersant (accounting for 2.0% of the mass of the mixed powder), 5g of diethylhexyl alcohol as defoamer (accounting for 1% of the mass of the mixed powder), 450g of ethanol as solvent (accounting for 90% of the mass of the mixed powder), 1000g of silicon nitride grinding balls (accounting for 200% of the mass of the mixed powder). In step 2), the first ball milling treatment time is 30h. In step 3), the second ball milling treatment time is 30h. In step 4), the degassing treatment time is 5h. In step 6), the debinding treatment temperature is 600°C, and the heating rate is 0.1°C / min-3°C / min. In step 7), the process control process is: maintain 1100°C for 120min, maintain 1200°C for 150min, maintain 1250°C for 180min, maintain 1300°C for 150min, maintain 1350°C for 200min, and maintain 1400°C and 1450°C for 300min each. During the nitriding process, nitrogen is introduced when the temperature rises to 1200°C, and the pressure at 1200°C is controlled to be 0.5MPa, 1250°C is 0.5MPa, 1300°C is 0.8MPa, 1350°C is 0.9MPa, 1400°C is 1.0MPa, and 1450°C is 1.2MPa. After maintaining 1200°C for 150min, the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.11, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.39, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.43, and the β-Si 3 N4 and α-Si 3 N 4 The mass ratio of β-Si was 0.64, and the β-Si was tested after maintaining 1400℃ for 300min. 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.73, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of is 0.78. In step 8), the sintering temperature is 1800°C and the temperature is kept for 6 hours. The silicon nitride material includes silicon nitride crystals, and there are grain boundary phases between the silicon nitride crystals. The grain boundary phases include a glass phase, and the glass phase includes Y, Mg, Si, O, and Ti.

[0116] Example 3

[0117] The preparation method of the silicon nitride material in Example 3 is substantially the same as that in Example 1, except that: in step 1), the sintering aid comprises Y 2 O 3 、MgO、Si 3 N 4 , the reinforcement phase includes TiC. Weigh 445.5g Si powder (accounting for 89.1% of the mixed powder mass), Y 2 O 3 Powder 22.5g (accounting for 4.5% of the mixed powder mass), MgO powder 19.5g (accounting for 3.9% of the mixed powder mass), Si 3 N 42.5g of powder (accounting for 0.5% of the mass of the mixed powder), 10g of TiC powder (accounting for 2% of the mass of the mixed powder), 141.5g of polyvinyl butyral binder (accounting for 28.3% of the mass of the mixed powder), 28.5g of diisooctyl phthalate plasticizer (accounting for 5.7% of the mass of the mixed powder), 7.5g of polyvinyl pyrrolidone dispersant (accounting for 1.5% of the mass of the mixed powder), 7.5g of diethylhexyl alcohol defoamer (accounting for 1.5% of the mass of the mixed powder), 500g of ethanol solvent (accounting for 100% of the mass of the mixed powder), 1000g of silicon nitride grinding balls (accounting for 200% of the mass of the mixed powder). In step 2), the first ball milling treatment time is 30h. In step 3), the second ball milling treatment time is 30h. In step 4), the degassing treatment time is 5h. In step 6), the debinding treatment temperature is 500℃. In step 7), the process control process is: maintain 1100℃ for 300min, maintain 1200℃ for 60min, maintain 1250℃ for 120min, maintain 1300℃ for 120min, maintain 1350℃ for 300min, and maintain 1400℃ and 1450℃ for 360min respectively. During the nitriding process, nitrogen is introduced when the temperature rises to 1200℃, and the pressure at 1200℃ is controlled to be 0.5MPa, 1250℃ is controlled to be 0.6MPa, 1300℃ is controlled to be 0.8MPa, 1350℃ is controlled to be 0.8MPa, 1400℃ is controlled to be 1.0MPa, and 1450℃ is controlled to be 1.0MPa. After maintaining 1200℃ for 60min, β-Si is tested 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.04, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.40, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.43, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.74, and the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio of β-Si was 0.65, and the β-Si 3 N 4and α-Si 3 N 4 The mass ratio of is 0.76. In step 8), the sintering temperature is 1700°C and the temperature is kept for 4 hours. The silicon nitride material includes silicon nitride crystals, and there are grain boundary phases between the silicon nitride crystals. The grain boundary phases include a glass phase, and the glass phase includes Y, Mg, Si, O, and Ti.

[0118] Example 4

[0119] The preparation method of the silicon nitride material in Example 4 is basically the same as that in Example 1, except that the D50 of the silicon powder is changed to 0.9 μm. 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 1.

[0120] Example 5

[0121] The preparation method of the silicon nitride material in Example 5 is basically the same as that in Example 1, except that the D50 of the silicon powder is changed to 6.5 μm. 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 1.

[0122] Example 6

[0123] The preparation method of the silicon nitride material in Example 6 is basically the same as that in Example 1, except that the D50 of the silicon powder is changed to 15 μm. 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 1.

[0124] Example 7

[0125] The preparation method of the silicon nitride material in Example 7 is basically the same as that in Example 1, except that the sintering temperature is changed to 1700°C. 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 1.

[0126] Example 8

[0127] The preparation method of the silicon nitride material in Example 8 is basically the same as that in Example 1, except that the reinforcing phase is changed to TiC. 3 N 4 and α-Si 3N 4 The mass ratio is substantially the same as that in Example 1.

[0128] Comparative Example 1

[0129] The preparation methods of the silicon nitride materials in Comparative Example 1 and Example 3 are basically the same, except that a small amount of Al-containing sintering aid is added to the sintering aid. 444.5 g of Si powder (accounting for 88.9% of the mass of the mixed powder) is weighed. 2 O 3 Powder 22.5g (accounting for 4.5% of the mixed powder mass), MgO powder 19.5g (accounting for 3.9% of the mixed powder mass), Si 3 N 4 2.5g of powder (accounting for 0.5% of the mixed powder mass), 10g of TiC powder (accounting for 2% of the mixed powder mass), and 1g of AlN powder (accounting for 0.2% of the mixed powder mass). 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 3.

[0130] Comparative Example 2

[0131] The preparation methods of the silicon nitride materials of Comparative Example 2 and Example 3 are basically the same, except that the D50 of the silicon powder is 18.3 μm, the binder polyvinyl butyral is 141.0 g (accounting for 28.2% of the mass of the mixed powder), the plasticizer diisooctyl phthalate is 36.0 g (accounting for 7.2% of the mass of the mixed powder), the dispersant polyvinyl pyrrolidone is 15.0 g (accounting for 3.0% of the mass of the mixed powder), the defoamer diethyl hexanol is 7.5 g (accounting for 1.5% of the mass of the mixed powder), and the solvent ethanol is 50 g (accounting for 100% of the mass of the mixed powder). 3 N 4 and α-Si 3 N 4 The mass ratio is substantially the same as that in Example 3.

[0132] Comparative Example 3

[0133] The preparation methods of the silicon nitride materials in Comparative Example 3 and Example 3 are basically the same, except that the nitridation reaction control process is as follows: in this process, the temperature is kept at 1100°C for 60 minutes and 1500°C for 180 minutes, and the temperature is increased from 1100°C to 1500°C at a rate of 0.5°C / min. During the nitridation process, the β-Si 3 N 4 and α-Si 3 N 4 The mass ratio is 1.23.

[0134] Comparative Example 4

[0135] The preparation methods of the silicon nitride materials of Comparative Example 4 and Example 3 are basically the same, except that the sintering treatment temperature is 1950° C. and the heat preservation time is 4 hours.

[0136] Comparative Example 5

[0137] The preparation method of the aluminum oxide material in this comparative example is basically the same as the preparation method of the silicon nitride material in Example 1, except that: in step 1), the mixed powder includes aluminum oxide and a sintering aid, and the sintering aid includes ZrO 2 、MgO、La 2 O 3 、Si 3 N 4 . Weigh Al 2 O 3 Powder 430g (accounting for 86% of the mixed powder mass), ZrO 2 62.5g of powder (accounting for 12.5% ​​of the mixed powder mass), 2.5g of MgO powder (accounting for 0.5% of the mixed powder mass), 2 O 3 Powder 2.5g (accounting for 0.5% of the mixed powder mass), Si 3 N 4 2.5g of powder (accounting for 0.5% of the mass of the mixed powder). 60.0g of polyvinyl butyral binder (accounting for 12% of the mass of the mixed powder), 60.0g of diethyl phthalate plasticizer (accounting for 12% of the mass of the mixed powder), 10.0g of polyvinyl pyrrolidone dispersant (accounting for 2% of the mass of the mixed powder), 5.0g of diethyl hexyl alcohol defoamer (accounting for 1.0% of the mass of the mixed powder), 300g of ethanol solvent (accounting for 60% of the mass of the mixed powder), 1000g of silicon nitride grinding balls (accounting for 200% of the mass of the mixed powder). In step 2), the first ball milling treatment time is 12h. In step 3), the second ball milling treatment time is 16h. In step 4), the degassing treatment time is 5h. In step 5), the belt speed of the casting machine is 120mm / min, and the temperature is set to 50℃, 60℃, 65℃, and 80℃ in four temperature zones. In step 6), the cast ceramic green sheets are stacked with boron nitride powder for isolation, and pre-sintered at 550°C in a debinding furnace with a heating rate of 0.1°C / min-3°C / min to obtain a debinding product. In steps 7) and 8), the debinding product is sintered in an air atmosphere at a temperature of 1600°C for 2 hours and then cooled by natural cooling.

[0138] Test example

[0139] 1. Density test: Refer to GB / T 3850-2015 Density determination method for dense sintered metal materials and cemented carbide to test the density of the ceramic substrate. The test sample size is a 10mm diameter disc.

[0140] 2. Bending strength test: refer to GB / T 6569-2006 fine ceramic bending strength test method, loading speed 0.5mm / min, measuring distance 30mm for testing.

[0141] 3. Thermal conductivity test: Use GB / T 22588-2008 flash method to measure thermal diffusivity or thermal conductivity and test thermal conductivity.

[0142] 4. Crystalline content test: β-Si is measured using JY / T 0587-2020 General Rules for Polycrystalline X-ray Diffraction Methods 3 N 4 and α-Si 3 N 4 The mass percentage of the crystalline phase.

[0143] 5. Grain size test: The microscopic grain structure of silicon nitride material was observed by field emission scanning electron microscope, and the short axis and long axis of the grains were sampled and tested by Image J software. The largest short axis grain size among 100 grains is the maximum short axis grain size, the smallest short axis grain size among 100 grains is the minimum short axis grain size, the largest long axis grain size among 100 grains is the maximum long axis grain size, the smallest long axis grain size among 100 grains is the minimum long axis grain size, the average value of the short axis size among 100 grains is the average short axis grain size, and the average value of the long axis size among 100 grains is the average long axis grain size.

[0144] 6. Vickers hardness HV10: The Vickers hardness HV10 of silicon nitride material is measured using GB / T 16534-2009 fine ceramic room temperature hardness test method.

[0145] 7. Method for testing elements in glass phase: Use transmission electron microscopy and high-resolution transmission electron microscopy to observe and test the composition and element distribution of the grain boundary glass phase.

[0146] Figure 3 This is a scanning electron microscope image of the silicon nitride material of Example 1 of the present invention.

[0147] Figure 4 This is a scanning electron microscope image of the silicon nitride material of Example 2 of the present invention.

[0148] Figure 5 This is a scanning electron microscope image of the silicon nitride material of Example 3 of the present invention.

[0149] Figure 6This is a scanning electron microscope image of the silicon nitride material of Comparative Example 3 of the present invention.

[0150] Figure 7 This is a scanning electron microscope image of the aluminum oxide material of Comparative Example 5 of the present invention.

[0151] from Figure 3-7 It can be seen that the grain sizes of the silicon nitride materials prepared in Examples 1-3 of the present invention are relatively small, while the grain sizes of the silicon nitride materials prepared in Comparative Examples 3 and 5 are relatively large.

[0152] Figure 8 This is a grain size distribution diagram of the silicon nitride material of Example 1 of the present invention.

[0153] Fig. 9 This is a grain size distribution diagram of the silicon nitride material of Example 2 of the present invention.

[0154] Fig.10 This is a grain size distribution diagram of the silicon nitride material of Example 3 of the present invention.

[0155] Fig.11 This is a grain size distribution diagram of the silicon nitride material of Comparative Example 3 of the present invention.

[0156] from Figure 8-11 It can be seen that the grain size distribution of the silicon nitride material prepared in Examples 1-3 of the present invention is relatively narrow, while the grain size distribution of the silicon nitride material prepared in Comparative Example 3 is relatively wide.

[0157] Fig.12 This is a physical picture of the silicon nitride ceramic green sheet of Comparative Example 2 of the present invention.

[0158] from Fig.12 It can be seen that the silicon nitride ceramic green sheet prepared in Comparative Example 2 has cracks and cannot be subjected to subsequent sintering treatment.

[0159] Fig.13 This is a physical picture of the silicon nitride material of comparative example 4 of the present invention.

[0160] from Fig.13 It can be seen that the silicon nitride material prepared in Comparative Example 4 is over-burned, silicon nitride decomposition occurs, the surface is rough and uneven, and it cannot be used as an electrostatic chuck.

[0161] Table 1

[0162]

[0163] The silicon nitride material provided by the present invention includes silicon nitride crystals, and the average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm. The small grain size can not only effectively reduce concentrated stress and block dislocation slip, but also reduce defects and discontinuities at grain boundaries and optimize phonon transmission paths, so that the silicon nitride material can have the characteristics of high hardness and high thermal conductivity.

[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon nitride material, characterized in that: The silicon nitride material includes silicon nitride crystals, and an average short-axis grain size of the silicon nitride crystals is less than or equal to 3.5 μm.

2. The silicon nitride material according to claim 1, characterized in that: The average long-axis grain size of the silicon nitride crystal is less than or equal to 8.5 μm; and / or, the difference between the maximum short-axis grain size and the minimum short-axis grain size of the silicon nitride crystal is less than or equal to 8.5 μm; And / or, the difference between the maximum long-axis grain size and the minimum long-axis grain size of the silicon nitride crystal is less than or equal to 10 μm.

3. The silicon nitride material according to claim 1 or 2, characterized in that: The thermal conductivity of the silicon nitride material is greater than or equal to 90 W / m·K; And / or, the Vickers hardness HV10 of the silicon nitride material is greater than or equal to 1600; And / or, the density of the silicon nitride material is greater than or equal to 3.21 g / cm 3 ; And / or, the flexural strength of the silicon nitride material is greater than or equal to 900 MPa.

4. The silicon nitride material according to any one of claims 1 to 3, characterized in that: The mass percentage of the β-Si3N4 in the silicon nitride crystal is greater than or equal to 95%.

5. The silicon nitride material according to any one of claims 1 to 4, characterized in that: There is a grain boundary phase between the silicon nitride crystals, and the grain boundary phase includes a glass phase, and the glass phase includes at least one of Mg, Ca, Zr, La, Ce, Y, Yb, Eu, Dy, Lu, B, and Ti.

6. A method for preparing the silicon nitride material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) contacting a raw material including silicon powder with a nitrogen source to perform a nitridation reaction to obtain a precursor containing silicon nitride; the precursor containing silicon nitride comprises β-Si3N4 and α-Si3N4, and the mass ratio of β-Si3N4 to α-Si3N4 is 0.57-0.86; 2) Sintering the precursor containing silicon nitride to obtain the silicon nitride material.

7. The preparation method according to claim 6, characterized in that: The raw material including silicon powder also includes at least one of a reinforcing phase, a sintering aid, a dispersant, a binder, a plasticizer, and a defoaming agent; The reinforcement phase includes TiC and / or TiN.

8. The preparation method according to claim 6 or 7, characterized in that: Before the nitridation reaction, the method further includes: sequentially performing a casting process and a debinding process on the raw material including silicon powder to obtain a debinding product; and contacting the debinding product with a nitrogen source to perform a nitridation reaction to obtain the precursor containing silicon nitride.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The D50 of the silicon powder is 0.9 μm-15 μm, preferably 2.0 μm-6.5 μm; And / or, the sintering temperature is 1700°C-1900°C.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The process of the nitridation reaction comprises: 1) contacting the raw material including silicon powder with a nitrogen source, and performing a first reaction at 1200° C.-1250° C. to obtain a first reaction product; wherein the mass ratio of β-Si3N4 to α-Si3N4 in the first reaction product is 0.04-0.54; 2) subjecting the first reaction product to a second reaction at 1300° C.-1350° C. to obtain a second reaction product; wherein the mass ratio of β-Si3N4 to α-Si3N4 in the second reaction product is 0.33-0.82; 3) subjecting the second reaction product to a third reaction at 1400° C.-1500° C. to obtain the precursor containing silicon nitride.

11. A structural member, characterized in that: The invention comprises the silicon nitride material according to any one of claims 1 to 5 or the silicon nitride material prepared by the preparation method according to any one of claims 6 to 10.

12. The structural member according to claim 11, characterized in that: The structural component is at least one of an electrostatic chuck, a ceramic substrate, a ceramic bearing ball, a ceramic bearing sleeve, and a protective tube.

Citation Information

Cited By

  • Silicon nitride material and preparation method therefor, and structural member

    WO2026124174A1